Excel Pro Tips 75+ Tips to go from Excel Beginner to Pro%% - Dutton, Chris (Packt Publishing, 2019)
Master 75+ Excel tips and techniques and become a certified POWER USER, with unique hands-on demos and real-world projects to help you wrangle, analyze, and visualize your data in Excel. About This Video Master some of the most powerful and effective tools and techniques used by Excel professionals Unique hands-on demos and real-world case studies Learn tools and techniques in quick, bite-sized lessons In Detail This course is not an introduction to Excel. It features some of the most powerful and effective tools and techniques used by Excel professionals, and shares them through crystal-clear demos and unique, real-world case studies. Unlike most Excel courses, this course is non-linear and constantly evolving, which means that you can jump to different sections or individual lectures freely. Each video is designed to be an independent and self-contained demo, to help you learn these tools and techniques in quick, bite-sized lessons. The Excel tips and techniques covered in this course fall into six categories: Productivity tips (navigation, flash fill, cell protection, advanced sorting & filtering, and more) Formatting tips (freeze panes, row/column grouping, advanced custom formats, and more) Formula tips (formula auditing tools, fuzzy lookups, detecting duplicates, randomization, and more) Visualization tips (sparklines, filled maps, custom templates, Excel form controls, and more) Pivot Table tips (slicers & timelines, custom layouts, value calculations, and more) Analytics tips (outlier detection, Monte Carlo simulation, forecasting, CUBE functions, and more) While the level of difficulty varies considerably, the demos generally start simple and become progressively more complex within each section. There are no strict prerequisites for this course, but keep in mind that some demos may be challenging without a strong foundational knowledge of underlying Excel concepts (such as Pivot Tables or formulas, for example). The codes are placed in the GitHub link as below- https://github.com/sanjanapackt/PacktPublishing-Excel-Pro-Tips-75--Tips-to-go-from-Excel-Beginner-to-Pro.